Catalyst-Free Oxidation of Sulfides to Sulfoxides by gem-Dihydroperoxide under Mild Conditions - Grabovskii, Stanislav A.; Andrijashina, Nadezhda M.; Lobov, Alexandr N.; Antipin, Arkadiy V.; Safiullin, Rustam L. (Synlett, 2023)
A facile and efficient method for the oxidation of sulfides (dialkyl, phenylalkyl, benzylalkyl) to sulfoxides under mild conditions without using any catalysts is reported. This method afforded a series of sulfoxides with good yields (>95%). The ready accessibility and low cost of the gem-dihydroperoxides will endow it with attractive applications in chemical synthesis as oxidants.
Keywords: sulfides; sulfoxides; gem-dihydroperoxides; oxidation; catalyst-free